From Awareness to Action: Decoding the Green Gap in Sustainable Fashion Consumption Using the Information-Motivation-Behavioral Skills - Tiara Nur Anisah; Eri Haryanto; Andika; Pooja Nanda; Daniel Wandika (Universitas Airlangga, 2026)
Objective: This study aims to decipher the